2019
DOI: 10.1097/md.0000000000018343
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for hiccups

Abstract: Background: A Hiccup is a common disease that often occurs along with other chronic or acute conditions. At present, there is a lack of feasible therapies for hiccups, and acupuncture is a treatment method with enormous clinical practice worldwide. Methods: Based on a pre-defined search strategy, we searched seven databases and screened them by two independent investigators, without language and publication status restriction from inception to date. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, several studies have shown that conservative therapy focused on eliminating vocal abuse and controlling the underlying cause of phonotrauma or irritation should be considered over surgery [12,13]. Suggested treatments for hiccups may vary according to the specific cause and include food restriction, physical maneuvers, behavioral therapy, pharmacological therapy, voice therapy, acupuncture, and interventional treatments as VNS and phrenic nerve blockade [5,6,14,15]. Noteworthy, a recent systematic review by Li et al highlighted the role of acupuncture as a neuromodulation-like regulator among patients with chronic hiccups [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that conservative therapy focused on eliminating vocal abuse and controlling the underlying cause of phonotrauma or irritation should be considered over surgery [12,13]. Suggested treatments for hiccups may vary according to the specific cause and include food restriction, physical maneuvers, behavioral therapy, pharmacological therapy, voice therapy, acupuncture, and interventional treatments as VNS and phrenic nerve blockade [5,6,14,15]. Noteworthy, a recent systematic review by Li et al highlighted the role of acupuncture as a neuromodulation-like regulator among patients with chronic hiccups [15].…”
Section: Discussionmentioning
confidence: 99%